2017
DOI: 10.4103/jiaps.jiaps_250_16
|View full text |Cite
|
Sign up to set email alerts
|

A sharp lesson: Duodenal perforation 2 months after ingestionof a pin

Abstract: An 11-year-old female child presented 2 months after accidentally swallowing her hijab pin, with right-sided abdominal pain. An X-ray showed that the pin was located in her right upper quadrant, and at laparoscopy, it was found to have eroded through her duodenum into her liver. Ingested pins should always be removed if not passed spontaneously within the first few days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Ingested foreign bodies generally pass through the gastrointestinal tract without complications. Less than 1% cause perforations [35][36][37][38]. Sharp and thin foreign bodies have been associated with a higher perforation risk.…”
Section: Foreign Bodiesmentioning
confidence: 99%
“…Ingested foreign bodies generally pass through the gastrointestinal tract without complications. Less than 1% cause perforations [35][36][37][38]. Sharp and thin foreign bodies have been associated with a higher perforation risk.…”
Section: Foreign Bodiesmentioning
confidence: 99%
“…Dalrymple et al reported a patient with a perforation of the duodenum and liver with a localized pus collection, who presented with mild abdominal pain 2 months after pin ingestion. 18 There has been one report of death in a patient with hijab pin ingestion, although the details of this case are not clear. 19 These cases reveal the importance of ensuring adequate follow-up for asymptomatic patients discharged from the hospital without proof of passing the pin.…”
Section: Figurementioning
confidence: 90%